2020
DOI: 10.1016/j.jeem.2019.102289
|View full text |Cite
|
Sign up to set email alerts
|

Superfund cleanups and children’s lead exposure

Abstract: This study evaluates the effect of EPA's Superfund cleanup program on children's lead exposure. We linked two decades of blood lead level (BLL) measurements from children in six states with data on Superfund sites and other lead risk factors. We used quasi-experimental methods to identify the causal effect of proximity to Superfund cleanups on rates of elevated BLL. We estimated a difference-in-difference model comparing the change in elevated BLL of children closer to versus farther from lead-contaminated sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Today, most residential properties have been remediated along with the smelting areas and some of the old mine sites [ 15 , 48 ]. Blood lead level concentrations among children living in nearby communities fell from approximately 64 to 2.7 μg/dL during 1974–2001 [ 11 , 50 ]. Yet, the region remains contaminated at abandoned mine sites and in the floodplains of creeks and rivers where the mine waste was dumped and continues to be distributed by high water events [ 28 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, most residential properties have been remediated along with the smelting areas and some of the old mine sites [ 15 , 48 ]. Blood lead level concentrations among children living in nearby communities fell from approximately 64 to 2.7 μg/dL during 1974–2001 [ 11 , 50 ]. Yet, the region remains contaminated at abandoned mine sites and in the floodplains of creeks and rivers where the mine waste was dumped and continues to be distributed by high water events [ 28 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the toxin impacts every organ of the body and even low levels of exposure are linked to chronic diseases such as diabetes and heart disease [ 5 , 7 , 8 , 9 ]. In fact, health organizations including the US Centers for Disease Control (CDC) and the European Food Safety Authority have concluded that there is no safe or “nontoxic” blood lead level [ 5 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these processes generate substantial disamenities for nearby residents, including increased exposure to lead and other pollutants (e.g. Currie et al, 2015a;Klemick et al, 2019).…”
Section: The Physiology Of Lead and Prior Workmentioning
confidence: 99%
“…25 In expectation, a child in a race county experienced a 0.087 IQ point decrease. Last, we link IQ to earnings following the procedure in Klemick et al (2019), which estimates that a 1 IQ point decrease for a three year old is associated with a present value earnings loss of $20,568 in 2019 dollars. 26 Combining these estimates, the costs of reduced IQ are $1,789 per child in race counties.…”
Section: Blood Lead Iq and Future Incomementioning
confidence: 99%
“…Today, most residential properties have been remediated along with the smelting areas and some of the old mine sites [31,33]. Blood lead level concentrations among children living in nearby communities fell from approximately 64 μg/dL to 2.7 μg/dL during 1974-2001 [34,35]. Yet, the Silver Valley remains contaminated at abandoned mine sites and in the floodplains of creeks and rivers where the mine waste was dumped and continues to be distributed by high flows.…”
Section: Study Areamentioning
confidence: 99%